2022
DOI: 10.3389/fnana.2022.1074310
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative sleep deprivation activates the paraventricular thalamic nucleus resulting in persistent postoperative incisional pain in mice

Abstract: BackgroundThe duration of postsurgical pain is closely correlated with perioperative stress. Most patients suffer short-term sleep disorder/deprivation before and/or after surgery, which leads to extended postsurgical pain by an undetermined mechanism. The paraventricular thalamus (PVT) is a critical area that contributes to the regulation of feeding, awakening, and emotional states. However, whether the middle PVT is involved in postoperative pain or the extension of postoperative pain caused by perioperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It allows our body to rest and speed up recovery. Previous studies have demonstrated that perioperative sleep disorders may increase the body's stress response, lead to greater hemodynamic changes, and affect the emotional state and ability to heal ( 40 ). However, preoperative sleep quality has not received sufficient attention in clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…It allows our body to rest and speed up recovery. Previous studies have demonstrated that perioperative sleep disorders may increase the body's stress response, lead to greater hemodynamic changes, and affect the emotional state and ability to heal ( 40 ). However, preoperative sleep quality has not received sufficient attention in clinical studies.…”
Section: Discussionmentioning
confidence: 99%